2015
DOI: 10.1542/peds.2013-1427
|View full text |Cite
|
Sign up to set email alerts
|

A Treatable Metabolic Cause of Encephalopathy: Cobalamin C Deficiency in an 8-Year-Old Male

Abstract: Neurologic regression in a previously healthy child may be caused by metabolic or neurodegenerative disorders, many of which have no definitive treatment. We report a case of a previously healthy 8-year-old boy who presented with a month-long history of waxing and waning encephalopathy and acute regression, followed by seizures. Evaluation for a metabolic disorder revealed methylmalonic acidemia and hyperhomocysteinemia of the cobalamin C type due to a single, presumed homozygous pathogenic c.394 C.T mutation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Typical medications for MMA include vitamin B12, L-carnitine, betaine, calcium foliate, vitamin B8 and special milk (excluding valine, threonine and methionine) ( 25 ). It has previously been suggested that angiotensin converting enzyme inhibitor should be prescribed for MMA patients with renal damage, as this drug may aid to reduce proteinuria and promote the recovery of renal function ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Typical medications for MMA include vitamin B12, L-carnitine, betaine, calcium foliate, vitamin B8 and special milk (excluding valine, threonine and methionine) ( 25 ). It has previously been suggested that angiotensin converting enzyme inhibitor should be prescribed for MMA patients with renal damage, as this drug may aid to reduce proteinuria and promote the recovery of renal function ( 26 ).…”
Section: Discussionmentioning
confidence: 99%